Asesmen Kompetensi Minimal (AKM) dalam Mewujudkan Sekolah Efektif di SMP Negeri 1 Kebumen - Kabupaten Kebumen Perspektif Manajemen Kurikulum dan Sistem Penilaian - Martiyono .; Rita Sulastini; Sri Handajani (LPPM IAINU Kebumen, 2021)
The objectives of this study are (1) to describe the planning, implementation, monitoring, evaluation, reporting and follow-up of the Minimum Competency Assessment (AKM) at SMP Negeri 1 Kebumen, Kebumen Regency and (2) to determine the success of the Minimum Competency Assessment (AKM) in realizing effective schools in SMP Negeri 1 Kebumen. The method used is school action research at SMP Negeri 1 Kebumen, Kebumen Regency in Semester 1 of the 2021/2022 academic year. The method of data collection was done by using observation, documentation, and interview techniques. The data analysis technique used is a qualitative descriptive technique with data validity techniques using triangulation of data collection techniques and sources. The research procedure includes (1) planning, namely preparation, socialization, and testing, (2) implementation, (3) observation, and (4) evaluation and reflection. Minimum Competency Assessment (AKM) at SMP Negeri 1 Kebumen Kebumen Regency is carried out through implementation procedures, namely (1) planning, which includes the formation of a work team, preparation of Standard Operating Procedures (POS), preparation of facilities and infrastructure, preparation of development instruments, socialization and strengthening capacity for teachers and administration, students, school committees and parents, as well as implementation trials, (2) implementation, and (3) monitoring, evaluation, reporting and follow- up. Minimum Competency Assessment (AKM) in realizing effective schools at SMP Negeri 1 Kebumen, which is characterized by (1) input efficiency, (2) process effectiveness, (3) output productivity (4) outcome relevance.